A STANDARDIZED ACHIEVEMENT TEST IN MATHEMATICS FOR GRADE 8 STUDENTS IN THE SCHOOLS DIVISION OF EASTERN SAMAR - Carlos B. Calvadores (Galaxy International Interdisciplinary Research Journal, 2022)
One of the important issues in any teaching and learning system is the quality of the students. The Department of Education in the Philippines ensures the continuous improvement of its systems to ensure that all the learners have access to quality basic education (DepEd Order No. 29, s.2017). Educational issue related to quality is the low level of student competence as a result of inadequate assessment system (Sidi as cited in Pandra, 2017).